Current and upcoming pharmacotherapy for non-alcoholic fatty liver disease. Issue 1 (19th September 2016) - Rotman, Yaron; Sanyal, Arun J
Abstract : Given the high prevalence and rising incidence of non-alcoholic fatty liver disease (NAFLD), the absence of approved therapies is striking. Although the mainstay of treatment of NAFLD is weight loss, it is hard to maintain, prompting the need for pharmacotherapy as well. A greater understanding of disease pathogenesis in recent years was followed by development of new classes of medications, as well as potential repurposing of currently available agents. NAFLD therapies target four main pathways. The dominant approach is targeting hepatic fat accumulation and the resultant metabolic stress. Medications in this group include peroxisome proliferator-activator receptor agonists (eg, pioglitazone, elafibranor, saroglitazar), medications targeting the bile acid-farnesoid X receptor axis (obeticholic acid), inhibitors of de novo lipogenesis (aramchol, NDI-010976), incretins (liraglutide) and fibroblast growth factor (FGF)-21 or FGF-19 analogues. A second approach is targeting the oxidative stress, inflammation and injury that follow the metabolic stress. Medications from this group include antioxidants (vitamin E), medications with a target in the tumour necrosis factor α pathway (emricasan, pentoxifylline) and immune modulators (amlexanox, cenicriviroc). A third group has a target in the gut, including antiobesity agents such as orlistat or gut microbiome modulators (IMM-124e, faecal microbial transplant, solithromycin). Finally, as the ongoing injury leads to fibrosis, the harbinger of liver-related morbidity and mortality, antifibrotics (simtuzumab and GR-MD-02) will be an important element of therapy. It is very likely that in the next few years several medications will be available to clinicians treating patients with NAFLD across the entire spectrum of disease.